Internal credit rating framework for real asset investment - Bae, Deog Sang (International Journal of Strategic Property Management, 2020)
Real asset investment, which is assumed to be worthier than traditional assets in regards to exposure to income volatility, has become central to investment portfolios in financial institutions. However, the features of illiquidity and uniqueness involved in an individual real asset deal require private investors to review the full dimensions associated with the transaction structure. Banks and global credit rating agencies assess the quality of products by relying heavily on qualitative research executed by human insights and experiences. Such an approach ensures the comprehensiveness of the review process but it requires excessive resources in time and money. This study presents an internal rating system that instantly screens features of a deal proposal and provides a rating compatible with the global rating standard. The result shows that the outcomes created by this model are mostly clustered from BBB to BB. These findings match the average ratings for real assets, as determined by global rating agencies, which strengthens the practicality of the proposed model.First published online 10 October 2019